Determining the Value of a Financial Unit of Account Basedon Composite Currencies : The Case of the Private Ecu - Folkerts-Landau, D.; Garber, Peter (Washington, D.C. : International Monetary Fund, 1994)
Evidence from the past three years indicates that the exchange rate between the private ECU and the official ECU Basket can deviate substantially from par. The value of the private ECU is driven by expectations that a future European Central Bank will enforce par convertibility between the private ECU and the official ECU basket of currencies. Meanwhile, no existing institutional arrangement limits the private ECU's value in terms of the Basket. This paper addresses the question of what determines the values of the private ECU and of private ECU interest rates. We show that an anticipation of a future fixing of the private ECU's value, together with the interest rate setting mechanism of the large-value ECU payment and clearing system, are sufficient to determine its value. The determination of the private ECU exchange rate provides the template for how to determine the value of any private composite currency, such as, for example, a private SDR.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet